MicroRNA-9 expression is a prognostic biomarker in patients with osteosarcoma - Xu, Shi-hong (BioMed Central, 2014)
BACKGROUND: The purpose of the present study was to examine the expression levels of microRNA-9 (miR-9) in osteosarcoma tissues and normal bone tissues, and investigate the relationships between miR-9 expression, clinicopathological features and the prognosis of patients with osteosarcoma. METHODS: The expression levels of miR-9 in osteosarcoma tissues and corresponding non-cancerous tissues were detected using a real-time quantitative assay. Differences in patient survival were determined using the Kaplan–Meier method and a log-rank test. A Cox proportional hazards regression analysis was used for univariate and multivariate analyses of prognostic values. RESULTS: Compared to non-cancerous bone tissues, the expression levels of miR-9 in osteosarcoma tissues were significantly elevated (P < 0.001). We found that the expression level of miR-9 was significantly associated with tumor size (P = 0.011), clinical stage (P = 0.009) and distant metastasis (P < 0.001). The Kaplan–Meier curve showed that patients with low miR-9 expression survived significantly longer than patients with high miR-9 expression (P = 0.0017). Multivariate analysis suggested that miR-9 expression level (P = 0.002) is an independent prognostic factors for overall survival. CONCLUSIONS: The findings of our study suggest that increased miR-9 expression has a strong correlation with the aggressive progression of osteosarcoma and its overexpression is a statistically significant risk factor affecting overall survival, suggesting that increased miR-9 expression could be a valuable marker of tumor progression and for prognosis of osteosarcoma.